Fertility Patterns of Native and Migrant Muslims in Europe. Issue 6 (1st June 2015) - Stonawski, Marcin; Potančoková, Michaela; Skirbekk, Vegard
Abstract: This study focuses on Muslim fertility in Europe. Evidence from 25 countries suggests that the Muslim total fertility rate is on average 47% higher than the national level. However, we find a significant difference in the level of fertility of native‐born Muslims and immigrant Muslims. The native‐born have a 19% higher total fertility rate, while immigrants have 62% higher fertility. Our main research question is whether religion is an important determinant of fertility outcome, or whether the other characteristics that are specific for Muslims in Europe (e.g. socio‐economics, migrant status, and religiosity) determine the observed difference in fertility. To answer this question, we focus on three case studies: Spain, where most Muslims are immigrants; Bulgaria, where most Muslims are native; and Greece, which has significant shares of both recent migrants and native Muslims. Our findings suggest that the immigrant status of Muslims and their socio‐economic status are more important than religion in terms of explaining their high fertility. Copyright © 2015 John Wiley & Sons, Ltd.